The moderating role of relational bonding in green supply chain practices and performance. Issue 4 (October 2017) - Li, Yong-Hui; Huang, Jing-Wen
Abstract: Previous research has paid attention to the effect of green supply chain practices on green innovation performance. However, little has been done to examine the substantive role of relational bonding in green supply chain management context. This study attempts to identify relational bonding as a potential moderator and examines the relationships between green supply chain practices, relational bonding, and green innovation performance. The results indicate that green supply chain practices and relational bonding are positively related to green innovation performance. Relational bonding moderates the relationship between green supply chain practices and green innovation performance. This study makes a contribution by integrating relationship marketing literature and green management literature. This study also provides practical implication for the essential role of relational bonding in green supply chain management. Highlights: This study extends the concept of relational bonding to green supply chain context. Green supply chain practices and relational bonding are beneficial for firms to achieve green innovation performance. Relational bonding moderates the relationship between green supply chain practices and green innovation performance.